1982
DOI: 10.1002/cne.902070411
|View full text |Cite
|
Sign up to set email alerts
|

The effects of environmental diversity on well‐fed and previously undernourished rats: I. Body and brain measurements

Abstract: Rats were undernourished from the 16th day of gestation to 25 postnatal days of age and then weaned on to an ad libitum diet. Around 35 days of age, 12 previously undernourished (PU) male pups were assigned to an "enriched environmental condition" (EC) and 12 to an "isolated environmental condition" (IC). Well-fed controls were similarly assigned. After 30 days in these conditions all rats were killed by perfusion with fixative.Body and "forebrain" weights, and forebrain lengths and widths, were determined for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In fact, it has been reported that environmental stimulation produces changes in structural, neurochemical and functional parameters in the central nervous system of the rat (26)(27)(28)(29). It has been suggested that these effects of early protein malnutrition may be partially reversed by environmental stimulation offered during malnutrition, or later during the nutritional recovery period (26,(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been reported that environmental stimulation produces changes in structural, neurochemical and functional parameters in the central nervous system of the rat (26)(27)(28)(29). It has been suggested that these effects of early protein malnutrition may be partially reversed by environmental stimulation offered during malnutrition, or later during the nutritional recovery period (26,(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…Other reports have also shown that environmental enrichment reduces ncurobehavioral abnormalities pro duced by nutritional deprivation in both hu mans [16,17] and laboratory animals [18], In addition, some experimental studies suggest that polysensorial stimulation carried out when 'brain growth spurt' is completed, i.e. after weaning, partially compensates for neocortical structural deficits produced by nutri tional deprivation [19][20][21][22][23][24], However, under the former experimental conditions, it has not been possible to demonstrate modifications at the main locus of synaptogenesis: the dendrit ic tree. Thus, as the highest rate of cytodiffer entiation is reached during the suckling peri od [25,26], the aim of the present study was to evaluate if sensorimotor stimulation ap plied during that time ameliorates both struc tural dendritic impairment and deteriorated exploratory behavior induced by undernutri tion.…”
Section: Introductionmentioning
confidence: 99%